Role of microcephalin at mitosis - Martin, Carol-Anne (The University of Edinburgh, 2011)
A large brain is one of the most distinguishing features of humans compared to other members of the animal kingdom. During mammalian evolution there has been a disproportionate enlargement of the brain relative to body size and this expansion has been particularly prominent during the past 3 million years of human lineage. This must be the consequence of adaptive genetic alterations during mammalian evolution, but the genes and molecular processes altered are essentially unknown. One approach for identifying candidate genes for brain size regulation is through characterisation of Mendelian disorders of brain development. In particular, primary microcephaly has received considerable interest as a model disease for studying brain size regulators because patients present with a profoundly reduced brain size but have no other malformations. Genetic studies have identified mutations in seven genes that can cause primary microcephaly. All the primary microcephaly proteins localise to the centrosome at some stage during the cell cycle and have roles in a diverse range of functions including centrosome maturation, centriole formation and microtubule organisation at the spindle pole. The precise mechanism leading to primary microcephaly is not known but a prevalent hypothesis is that centrosome dysfunction disrupts mitosis of neural progenitor cells. Despite there being strong evidence in support of this hypothesis for most primary microcephaly genes, MCPH1 (the first primary microcephaly gene to be identified) always appeared to be functionally distinct from other primary microcephaly proteins. Most work on MCPH1 has focussed on its role in the DNA damage response and cell cycle timing rather than on its mitotic role. As a result, the aim of this thesis is to perform a detailed analysis of MCPH1 function during mitosis. In this thesis, three isoforms of MCPH1 were characterised and their localisation, expression and stability examined. It was established that MCPH1 is highly regulated during mitosis. MCPH1 transcript and protein levels vary significantly throughout the cell cycle and MCPH1 protein is targeted for degradation late in mitosis. In addition, MCPH1 is hyperphosphorylated during mitosis (in prometaphase-arrested cells) suggesting that phosphorylation could potentially regulate MCPH1 mitotic function. Twelve mitotic phosphorylation sites were identified by phosphopeptide mapping, many of which were CDK1 and PLK1 consensus sites. Both PLK1 and CDK1 also contribute to MCPH1 phosphorylation in vivo. Although MCPH1 non-phosphorylatable mutants localise normally during mitosis, binding to interaction partners may be affected which may have functional consequences. During mitosis MCPH1 localises to the centrosomes and kinetochores. Consistent with this localisation, RNAi-mediated knockdown of MCPH1 leads to metaphase arrest with multipolar spindles, major defects in chromosome alignment and loss of chromatid cohesion. In addition, MCPH1 deficient mouse embryonic fibroblast cells also demonstrate similar chromosome alignment defects, strengthening this finding in an independent system. Live-imaging of MCPH1 depleted cells demonstrate that a normal bipolar spindle and metaphase plate are initially formed, but subsequently chromosomes and chromatids drop off the metaphase plate and eventually the spindle collapses. This suggests that the primary function of MCPH1 is to allow timely progression through metaphase, possibly by mediating kinetochore-microtubule attachments to satisfy the spindle activated checkpoint. Therefore my work describes several roles for MCPH1 in mitosis (centrosome stability, chromosome alignment and metaphase progression) suggesting that its role in mitosis could result in primary microcephaly in a number of different ways.
Keywords: Primary microcephaly; MCPH1; Mitosis